(.Effect of irrigating iron on vegetative and genetic parameters of five cultivars of the faba bean (Vicia faba L - Hayali, Arwa Ahmed Ibrahim; Hammad, Hamid Saleh; Aziz, Imad Khalaf (Journal of agricultural, environmental and veterinary sciences, 2018)
experimental field experience during the agricultural season 2016 to study the estimation of genetic parameters for varieties of the faba bean Under the influence of irrigated iron spry and the study included two factors ; The first is irrigated iron (13% iron W / W) and Add on three levels of 0 g. l-1 , 1 g. l-1 , 2 g. l-1 , and the second factor is five varieties of the faba bean and its Lortolano, Aquadulce, Luz de otono, Superaguadulce and the local class Hawija , And the study included 15 treatments , The results were statistically analyzed in split plot system within the design of complete random sector (R. C. B. D. (and three replicates and the results were compared using the Dunkin multidisciplinary test at a potential of 0. 05. The results showed that the cultivated plants at the level of irrigated iron were higher than 1 g. l-1 in plant heigh and total number of flowers , and the plants planted at the level of sprying 2 g. l-1 in the number of flowers in the cluster. The varieties differed significantly in most traits , Lortolano is superior to plant height , Luz de Otono is superior to the total number of flowers , While Hawijah gave the highest values in the number of major branches in the plant and the number of levels in the plant and the number of flowers in cluster.